Mistenksomhetens spiral - Maja Viktoria Spigseth Vestad (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In March and April 2020, at the earliest stages of the COVID-19 pandemic, the Norwegian government prohibited overnight stays at secondary homes as an early measure to prevent the spread of the virus. Violations of the ban carried penalties of up to 6 months in prison. Popularly dubbed the Cabin Ban, the law catalysed national debate, and violations of the ban generated massive public interest. This article recounts local conflicts sparked by the ban in four Norwegian «cabin municipalities», as described by residents, local politicians and cabin owners. It identifies the notion of autochthony as a central tool in  understanding why some chose to breach the ban, why local residents mobilised against cabin owners, and why the conflict escalated to the extent it did.